PELANGGARAN KODE ETIK PADA PEMBERITAAN MEDIA SOSIAL INTAGRAM (KONFLIK ETNIS ROHINGNYA) - Yulianto, Luqman; Rochim, Achludin Ibnu; Hakim, Lukman (Universitas 17 Agustus 1945 Surabaya, 2018)
Mass media has a very important role in disseminating information, news, and knowledge to the public. Social media is a new medium that is now the most widely used by the public. Instagram is one of the many social media available. Social media has now switched functions where the main function is to communicate, switch functions that are used to express anger, say hate (hate spech), cyber bullying, Cybercrime even to the problem of racial intolerance. There are not many other cases in Instagram social media users who violate the code of ethics and violate the ITE Law. There is not much to the point of legal problems. Therefore, to prevent the negative impact, Instagram social media users should understand and implement the ethics of communication. From this problem the researcher aims to find out how the Ethical Violations of Instagram Social Media News (Rohingnya Ethnic Koflik). This research is descriptive with a qualitative approach. Where researchers collect secondary data because researchers cannot find data directly from the first source. Where this data is in the form of seven photos analyzed using theory of utilizationism, code of ethics (policy Instagram), Law on ITE. From the results obtained in this study, users violated Instagram policies and the code of ethics has sadism and violence content. As for Instagram policy, and this ITE law is in accordance with the principle of Utilitarism, which is to produce the greatest possible consequences for the worst consequences. The effect of this theory of utilitarianism makes injustice to other Instagram social media users.Keywords: Instagram, Ethics, ITE Law, Code of Ethics, Rohingnya Ethnicity.